Pengaruh dosis pupuk kompos terhadap pertumbuhan dan produksi Rumput Odot (Pennisetrum Purpureum Cv. Mott) sebagai pakan ternak - Junaidi; Meriksa Sembiring (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
This study aims to examine the effect of applying various doses of compost fertilizer on the growth and production of dwarf elephant grass (Pennisetum purpureum cv. Mott) as animal feed. This study used a non-factorial Completely Randomized Design (CRD) with five doses of compost treatments (0 kg, 0.5 kg, 1 kg, 1.5 kg, and 2 kg per plot) and five replications. Parameters observed included stem diameter, plant height, number of tillers, leaf length, and fresh and dry forage production. The data obtained was tested by Analysis of Variance (ANOVA), followed by the Smallest Real Difference (SRD) test at a confidence level of 95%. The results showed that compost application had a significant effect (p<0,05) on all growth parameters of dwarf elephant grass. The compost dose of 2 kg/plot gave the best results with significant increases in stem diameter, plant height, number of tillers, leaf length, and fresh and dry forage production. In conclusion, the use of compost fertilizer is an effective alternative to increase the productivity of dwarf elephant grass in a sustainable manner.